Sensory processing patterns affect headache severity among adolescents with migraine - Genizi, Jacob (J Headache Pain, 2020)
OBJECTIVE: To evaluate the relationship between pain catastrophizing level, sensory processing patterns, and headache severity among adolescents with episodic migraine. BACKGROUND: Catastrophizing about pain is a critical variable in how we understand adjustment to pain and has a unique contribution in predicting pain intensity. Recent reports found that migraine is also related to enhanced sensory sensitivity. However, the relationship between pain severity, pain catastrophizing level and sensory sensitivity requires greater study especially among adolescents. METHODS: Participants were 92 adolescents aged 13–18 years, 40 with episodic migraine and 52 healthy controls. The migraine patients were prospectively recruited from outpatient pediatric neurology clinics. All participants completed the Adolescent/Adult Sensory Profile (AASP), and the Pain Catastrophizing Scale for children (PCS-ch). The migraine groups also completed the PedMIDAS, which measures Headache related disability. RESULTS: Adolescents with migraine had significantly lower tendency to seek sensory input than healthy controls. Elevated rumination and helplessness correlated with higher migraine pain severity. Tendency to avoid sensory input predicted the migraine related disability level. They also significantly higher pain catastrophizing level than healthy controls, as seen in enhanced rumination (p ≤ 0.001) and helplessness (p ≤ 0.05). CONCLUSIONS: Sensory processing difficulties are common among adolescents with episodic migraine. Sensory avoidance may be related to pain experience, and pain catastrophizing and disability level. TRIAL REGISTRATION: ISRCTN ISRCTN73824458. Registered 28 September 2014. retrospectively registered.